Lovecraftian Elements in the Writing of ‘Three Icons of Dongbei Renaissance’ - Wang, Aiqing (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2024)
Literary works based on Dongbei (China’s Northeast) or composed by Dongbei-born writers have been playing a preponderant role in modern Chinese literature. There is a recent resurgence of Dongbei-born writers who are collectively referred to as ‘neo-Dongbei writers’, exemplified by ‘three icons of Dongbei Renaissance’, aka ‘three swordsmen in the Tiexi District’. Notwithstanding reality-oriented depictions pertaining to social issues such as redundancy and dipsomania, fiction composed by Ban Yu, Zheng Zhi and Shuang Xuetao bears resemblance to Cthulhu Mythos. To be more specific, the three leading neo-Dongbei writers portray preternatural creatures, and their narratives convey fear of the unknown and nameless approximations of form.